2015
DOI: 10.1007/s11517-015-1247-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of different plate configurations for distal humerus osteosynthesis

Abstract: Fractures of the distal humerus are most commonly fixed by open reduction and internal fixation, using plates and screws, either in a locking or in a non-locking construct. Three different plating systems are commonly used in practice. The most important differences between them are in plate orientation, which affects both the rigidity of the osteosynthesis and invasiveness of the surgical procedure. Unfortunately, there is no common agreement between surgeons about which plate configuration brings the best cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
19
1
2
Order By: Relevance
“…As expected from previous studies [8,[21][22][23]] the 180°p arallel configurations demonstrated a higher stiffness than the 90°perpendicular configurations for the axial loading mode. This biomechanical advantage of parallel plating, has been confirmed by good clinical results [24].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As expected from previous studies [8,[21][22][23]] the 180°p arallel configurations demonstrated a higher stiffness than the 90°perpendicular configurations for the axial loading mode. This biomechanical advantage of parallel plating, has been confirmed by good clinical results [24].…”
Section: Discussionsupporting
confidence: 85%
“…These features aim at rigid stability to allow early mobilization as well as adequate stiffness to stimulate fracture healing [5]. The preferred plating techniques for comminuted distal humeral fractures include the Mayo clinic configuration (180°between plates) with parallel plate fixation and medial and lateral plate positioning as well as the AO/ASIF configuration (90°angle between plates) with perpendicular plate fixation and medial and postero-lateral plate positioning [3,[6][7][8][9]. Parallel orientation of the plates seemed biomechanically superior [10], but for the translation to the clinical setting the soft tissue envelope and Patrick A. Varady and Christian von Rüden contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Further biomechanical investigations that differentiated between fracture patterns with or without bone loss, suggest that in cases with a gap in between fragments, the 180°plate configuration shows the highest rigidity, followed by the perpendicular and a dorsal arrangement. On the other hand, no significant differences in rigidity between the three fixation configurations could be found in the case of no gap in between the bone fragments [51].…”
Section: Plating Options In Distal Humerus Fracturesmentioning
confidence: 74%
“…3 From biomechanical experiments on the fixation of the distal humerus, we know that parallel plating with inter-digitation of screws in the bone fragments is the optimal construct for stability of the fixation. 5 Other advantages of our technique are: avoidance of iatrogenic damage to the articular cartilage of the condyles, as screws are not inserted through the articular surface; superior pull-out strength and stability of fixation through the use of locking plates and screws versus lag screws only; and adequate exposure of the fracture and unobstructed visibility due to the patellar osteotomy.…”
Section: Discussionmentioning
confidence: 99%